Visitors’ attitude towards potential natural risks at Sungai Tekala Recreational Forest - Sabri, Syazlin Zulaikha (2019)
Visitors’ attitudes towards natural risk is paramount in any recreational area, especially in the forest settings such as recreational forest. This research determines visitors’ attitudes towards the potential natural risks at Sungai Tekala Recreational Forest. The study involved 200 respondents who were visitors to the recreational forest. Self-reported questionnaire developed based on the ABC Model of Attitude were used to determine visitors’ attitude towards potential natural risks. The findings of the study showed that respondents have highest attitude mean score for the natural risks of leptospirosis, flash flood and soil erosion at recreational forest. However, visitors have low attitude mean score on the potential risk of wind. Results also show that cognitive and affective construct are positively and strongly correlated to behaviour. Thus, providing knowledge and influencing emotion can be used to influence appropriate visitors’ behaviour towards the potential natural risks.